ALUMINA SOLUBILITY IN ORTHOPYROXENE COEXISTING WITH SAPPHIRINE AND QUARTZ - Hollis J.A.; Harley S.L. (My University, 2003)
The solubility of alumina in orthopyroxene coexisting with sapphirine and quartz was determined over the P–T interval 1,250–1,350 °C and 10–16 kbar in the system MgO–Al2O3–SiO2. Five isobaric experiments were reversed at 12 kbar at 25 °C intervals between 1,250 and 1,350 °C, and two isothermal experiments at 1,325 °C at 14 and 16 kbar. These constrain the P–T–X relationships of the reaction: \({\rm Mg - Tschermak's}\;{\rm orthopyroxene = Mg - sapphirine}_{{\rm 221}} \;{\rm + quartz}\) . The reaction is strongly temperature dependent and slightly pressure dependent (dP/dT=ca. 94 b K–1) and alumina in orthopyroxene increases by ca. 1 wt% per 26 °C over the temperature interval studied. No corresponding compositional trend in sapphirine was resolvable, an effect attributed to only small changes in alumina solubility with temperature and sluggish kinetics of sapphirine. Entropy calculations for sapphirine based on a recent dataset and minimum constraints from an oxide sum approach fall within the 90% confidence limits of our data, but above a linear-best fit of our data. The latter discrepancy suggests that disequilibrium in sapphirine and/or configurational disorder in orthopyroxene may have been important in the experiments. When taken into account these factors bring our data into reasonable agreement with an oxide sum calculation.
Keywords: Orthopyroxene